Community health insurance amidst abolition of user fees in Uganda: the view from policy makers and health service managers - Criel Bart; Basaza Robert K; Van der Stuyft Patrick (BMC, 2010)
Abstract Background This paper investigates knowledge of Community Health Insurance (CHI) and the perception of its relevance by key policy makers and health service managers in Uganda. Community Health Insurance schemes currently operate in the private-not-for-profit sector, in settings where church-based facilities function. They operate in a wider policy environment where user fees in the public sector have been abolished. Methods Semi-structured interviews were conducted during the second half of 2007 with District Health Officers (DHOs) and senior staff of the Ministry of Health (MOH). The qualitative data collected were analyzed using the framework method, facilitated by EZ-Text software. Results There is poor knowledge and understanding of CHI activities by staff of the MOH headquarters and DHOs. However, a comparison of responses reveals a relatively high level of awareness of CHI principles among DHOs compared to that of MOH staff. All the DHOs in the districts with schemes had a good understanding of CHI principles compared to DHOs in districts without schemes. Out-of-pocket expenditure remains an important feature of health care financing in Uganda despite blanket abolition of user fees in government facilities. Conclusion CHI is perceived as a relevant policy option and potential source of funds for health care. It is also considered a means of raising the quality of health care in both public and private health units. To assess whether it is also feasible to introduce CHI in the public sector, there is an urgent need to investigate the willingness and readiness of stakeholders, in particular high level political authorities, to follow this new path. The current ambiguity and contradictions in the health financing policy of the Uganda MOH need to be addressed and clarified.